Pore Structure and Fractal Characteristics of Shale under the Control of Bedding and Size: A Case Study of Shale from the Longmaxi Formation in China - Yao Cheng; Yifeng Xie; Yulin Ma; Yanlin Zhao (Advances in Civil Engineering)
In this study, the pore structure and fractal characteristics of shale samples with different bedding directions and sizes from the Longmaxi Formation of the Changning block in the Sichuan Basin were investigated by using CT imaging and low-temperature nitrogen adsorption experiments. The pore morphology, pore structure characteristics, relationships between the fractal dimensions and pore parameters, and effect of the size and bedding direction on pore morphology and various pore parameters were explored. In terms of pore structure characteristics, we found that the pores of shale samples were well developed and connected, forming a large number of pore clusters. The pores were mainly open pores and mesopores, which contributed the most to the specific surface area of the pores. Two fractal dimensions D1 and D2 were calculated from nitrogen adsorption data at relative pressures of 0–0.45 and 0.45–1, using the FHH method. These fractal dimensions characterized the pore surface and pore structure complexity, respectively. D1 ranged from 2.773 to 2.923, with a mean value of 2.821, and D2 varied from 2.853 to 2.899, with a mean value of 2.874. These variations indicated that there were irregular pore surfaces and sophisticated pore structures in the shale. The sample size and bedding direction had a significant impact on pore morphology and various pore parameters. Several pore characteristics of the vertical samples were superior to those of the horizontal samples. With an increase in size, the pore distribution became more uniform, the number of pore clusters increased, and the connectivity between pore clusters was enhanced. There was a good positive correlation between the fractal dimension D2 and specific surface area and moderate positive correlation between D2 and porosity and between D2 and pore volume. However, the fractal dimension D1 had a weak negative correlation with porosity and specific surface area and moderate negative correlation with pore volume. Moreover, both D1 and D2 tended to decrease with increasing average pore diameter.